2012
DOI: 10.1097/ico.0b013e31823f8a71
|View full text |Cite
|
Sign up to set email alerts
|

Candida Keratitis

Abstract: Candida is a new concern in developing countries like India. We are concerned about the poorer outcome, probably resulting from our unpreparedness and failure of medical therapy leading to more complication and requiring surgical intervention in higher numbers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Yeast keratitis is not known to respond favourably to natamycin and Chlorhexidine. 34 This particular patient was a previously undiagnosed HIV positive patient, he presented a few weeks later with another infiltrate in his only remaining eye which we successfully treated with topical amphotericin B 0.15%. 35 …”
Section: Discussionmentioning
confidence: 91%
“…Yeast keratitis is not known to respond favourably to natamycin and Chlorhexidine. 34 This particular patient was a previously undiagnosed HIV positive patient, he presented a few weeks later with another infiltrate in his only remaining eye which we successfully treated with topical amphotericin B 0.15%. 35 …”
Section: Discussionmentioning
confidence: 91%
“…It was not possible to enrol controls for 45 cases because of several reasons. These included: not at home at the agreed time of the home visit (11), wrong home address (4), died (1), uncooperative village members (20), case address too far (9). The cases without controls were dropped from the matched risk factor analysis.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13] Diabetes Mellitus (DM) has been the most commonly reported systemic risk factor, especially following keratoplasty or corneal trauma. [19][20][21] In the few studies from SSA on the risk factors for MK, suggested factors include trauma and use of TEM. [22][23][24] The other risk factors reported in the literature are steroid use, severe staphylococcal eyelid infections and the HIV positive cases.…”
Section: Introductionmentioning
confidence: 99%
“…Fungal keratitis (FK) is a severe infectious corneal disease in developing countries [1][2][3]. In China, more than 50% of infectious keratitis cases are the result of a fungal infection [4].…”
Section: Introductionmentioning
confidence: 99%